Bacterial Colonization in COPD Patients Admitted to a Rehabilitation Respiratory Unit and Impact on Length of Stay: A Real-Life Study. (2nd November 2018) - Vitacca, Michele; Marino, Simona; Comini, Laura; Fezzardi, Linda; Paneroni, Mara
Abstract: Bacterial colonization is a well-known phenomenon in acute care, but scant information is available regarding the rehabilitation setting. We retrospectively analyzed, in COPD patients admitted to a Respiratory Rehabilitative unit in 2010, the number of cultures requested, of positive cultures, and of cultures showing multiple drug resistant (MDR) organisms. We also compared hospital admissions (HA) with versus without positive cultures and with versus without MDR and investigated which baseline variables may predict length of stay (LOS) > 30 days. Of 286 COPD admissions (involving 269 patients, age 71 ± 11 years, males 66%), culture samples were requested in 62 (22%). The rate of colonization and of MDR organisms was 61 and 39%, respectively. Patients with a positive culture had a worse clinical condition and disability, and were more frequently tracheostomized, on invasive mechanical ventilation (MV) and admitted from/discharged to acute care. Patients with MDR cultures showed a lower exercise tolerance. Factors predicting LOS > 30 days were the presence of comorbidities, invasive MV, age > 65 years, and lower functional status, but not a positive culture or MDR presence. To our knowledge, this is the first real-life Italian study investigating the epidemiology of colonization and the association between colonization and LOS in a respiratory rehabilitation setting. Further investigation is necessary to clarify the relationship between colonization burden and patients' baseline clinical status and outcomes.